TEKNIK RELAKSASI NAFAS DALAM UNTUK MENGURANGI NYERI PADA PENDERITA HIPERTENSI - Amri, Novita (Jurnal Abdimas Saintika, 2024)
Hypertensiom is a cause of premature death throghout the world and has a fairly hig mortality rate which affects a person’squality and productivty. The World Health Organization (WHO) states that people with hypertension continue to increase every year, by 2025 it is estimated that hypertension sufferers will reach 1.5 billion and every year hypertension sufferers with complications will die at 9.4 million.the problem often experienced by hypertension patients is pain.   The pain can be reduced one of them using deep breathing techniques. The deep breath relaxation technique was breathing slowly and used the diaphragm, allowing the abdomen to slowly lift and the chest to expand fully. The purpose of this counseling is so that parents are able to understand the problem of  ypertension  and how to prevent it. The method used is Lectures and Questions and Answers with leaflets and LCD media. Therefore, in this case prevention efforts are needed, one of which is counseling on how to prevent  headches due to hypertension.Key Word : Hypertension, Pain, Deep breathing